Simulation of free piston linear engine motion with different intake and exhaust port positions - Ahmad Kamal Ariffin,; Nik Abdullah Nik Mohamed,; Syarizal Fonna, (2006)
This paper presents the simulation of two-stroke free piston linear engine motion consisting of combustion and air-kickback chambers. Dynamic and gas-dynamic models for slider-piston motion are presented. The influence of the intake and exhaust port position on the engine performance is explored. Using chosen variables, the motion of two-stroke free piston linear engine is successfully simulated. It shows that the velocity profile of slider-piston motion is far from sinusoidal. The comparison between both simulations with different location of intake and exhaust port reveals that the slider-piston velocities are not similar. Slider-piston velocity of model 2 with intake and exhaust port at the top of the cylinder block is 19 % higher than model 1 (intake and exhaust port at the cylindrical-side of cylinder block). Although that was the case, model 1 has an advantage in a way that it does not need valves and openclose valves system